Effect of Selected Stilbenoids on Human Fecal Microbiota - Jaimes, Jose D; Jarosova, Veronika; Veselý, Ondřej; Mekadim, Chahrazed; Mrazek, Jakub; Marsik, Petr; Killer, Jiri; Smejkal, Karel; Kloucek, Pavel; Havlik, Jaroslav (Molecules, 2019)
Dietary phenolics or polyphenols are mostly metabolized by the human gut microbiota. These metabolites appear to confer the beneficial health effects attributed to phenolics. Microbial composition affects the type of metabolites produced. Reciprocally, phenolics modulate microbial composition. Understanding this relationship could be used to positively impact health by phenolic supplementation and thus create favorable colonic conditions. This study explored the effect of six stilbenoids (batatasin III, oxyresveratrol, piceatannol, pinostilbene, resveratrol, thunalbene) on the gut microbiota composition. Stilbenoids were anaerobically fermented with fecal bacteria from four donors, samples were collected at 0 and 24 h, and effects on the microbiota were assessed by 16S rRNA gene sequencing. Statistical tests identified affected microbes at three taxonomic levels. Observed microbial composition modulation by stilbenoids included a decrease in the Firmicutes to Bacteroidetes ratio, a decrease in the relative abundance of strains from the genus Clostridium, and effects on the family Lachnospiraceae. A frequently observed effect was a further decrease of the relative abundance when compared to the control. An opposite effect to the control was observed for Faecalibacterium prausnitzii, whose relative abundance increased. Observed effects were more frequently attributed to resveratrol and piceatannol, followed by thunalbene and batatasin III.
Keywords: metagenom; feces; Feces; Gastrointestinal Microbiome; Molecular Structure; RNA, Ribosomal, 16S; stilbeny; lidé; Stilbenes; fermentace; metagenomika; Metagenome; Phylogeny; molekulární struktura; Metagenomics; střevní mikroflóra; Fermentation; fylogeneze; RNA ribozomální 16S; Humans